Popular Markets as Spaces for the Development of Sociocultural Processes in the Americas - Ángel-Bravo, Rafael (Sociedad y Economía, 2024)
Introduction Popular or central markets in Latin America are fundamental settings for the commercial exchange of goods and services. Moreover, they serve as spaces for the preservation and transmission of traditional and folkloric knowledge and practices, hosting a wide array of cultural heritage expressions. Objective This research-creation project seeks to recognize the cultural value of these settings through the various categories of goods and expressions present, considering the influence of social, geographical, and human factors inherent to their cultural nature. Methodology The research-creation project is developed through direct experience, photographic exploration, bibliographic review, and a taxonomic approach to the products and practices found in these spaces. Photography is employed as a tool for both data collection and visual creation. Results Through a series of phases, it was possible to identify unifying and differentiating factors among several markets in the northern, central, and southern regions of the Americas. A taxonomy of the goods and practices present was established, revealing a set of social, multicultural, and intercultural processes materialized in the various elements housed within these spaces. Conclusiones The observation, documentation, and classification of the goods and practices present in popular markets allow for the identification of multiple multicultural and intercultural processes, acknowledging the value of these spaces as sites of memory and repositories of knowledge.